PENGARUH INTEGRITAS, OBYEKTIVITAS, KERAHASIAAN, KOMPETENSI, DAN PENGALAMAN KERJA TERHADAP KINERJA AUDITOR PADA INSPEKTORAT PROVINSI RIAU - Ulfa Indri Utami; Kamaliah -; Rofika - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The population in this study are all inspectorate personnel who conduct financial audit in Riau province inspectorate. Of the 40 respondents, there are 4 people who did not return the questionnaire so that this research involved 36 respondents, the method of data collection using survey method through a questionnaire containing items statement. Methods of data analysis done in the form of test quality and test data normality. To test the effect used analysis tools SPSS version 17.0.The results showed that: 1) the integrity of the variables affect the performance of auditors in Riau Provincial Inspectorate. 2) variables affect the performance of the auditor's objectivity in the Riau Provincial Inspectorate. 3) variables affect the performance of the auditor's confidentiality at Riau Provincial Inspectorate .4) variables affect the performance of the auditor's competence in Riau Provincial Inspectorate. 5) work experience variables affect the performance of auditors in the Riau Provincial Inspectorate.Keywords: integrity, obyejtivitas, confidentiality, competence, andwork experience,performanceofauditors